Developing a Differentiated Learning-Based E-Module to Support Immune System Learning in Undergraduate Biology - Miftakhul Huda; Budhi Utami; Akhmad Sukri; Deni Hadiana; Agus Muji Santoso; Poppy Rahmatika Primandiri (Biosel Biology Science and Education, 2026)
The diversity of students’ interests, readiness, and learning profiles presents challenges in teaching complex biological concepts such as the immune system. Differentiated learning offers a strategy to address these differences by adapting content, processes, and learning products. This study aimed to develop and evaluate a differentiated learning-based electronic module (e-module) for undergraduate biology students. This study employed Educational Design Research based on the Plomp and Nieveen model, consisting of three phases: preliminary research, prototyping, and assessment. Data were collected through needs analysis questionnaires, expert validation sheets, student response questionnaires, and learning outcome assessments. The preliminary phase indicated that 82.6% of students strongly needed e-module-based learning materials. In the prototyping phase, the module achieved high validity scores from material experts (91.2%, very valid), media experts (79.16%, fairly valid), and practitioners (89%, very valid). Small-group testing showed very positive student responses (87%, very good). In the assessment phase involving undergraduate students, the average learning outcome was moderate, with variation across performance levels. The results indicate that the developed e-module is feasible and has the potential to support student engagement and may contribute to conceptual understanding. However, improvements in usability, assessment design, and the duration of implementation are required to enhance its effectiveness.  Keywords: Differentiated Instruction, E-Learning Module, Immune System, Educational Design Research